Ivan Karlov’s “Tsaritsyn Anabasis - Matvei I. Davydov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2017)
This paper acquaints the historians with a curious incident that took place in Suzdal in 1674. The present case surprisingly resembles a well-known plot twist of Jaroslav Hašek’s novel The Fateful Adventures of the Good Soldier Švejk During the World War – so called “Budějovice anabasis”, the protagonist’s epic grueling trek around Southern Czechia in the search for his regiment, which billeted in Budějovice. But if Švejk, despite all the vicissitudes, finally managed to achieve the ultimate objective successfully, Suzdal resident Ivan Karlov – a troublemaker and drunkard, sentenced to exile by local writ office and driven out from the city under the supervision of two constables to Tsaritsyn – conversely, some time later all of a sudden returned back to Suzdal teamwise with the convoy. The analysis of that episode revealed two facts worth mentioning. First of all, Suzdal writ office had a decentralized organizational structure: voyevoda’s court was located within the city whilst minor clerks worked apart from him at the Intercession of Theotokos convent. And secondly, it should be emphasized that for much of the 17th century not the voyevoda himself but the convent’s external administrator played the leading role in the writ office’s business routine. Expectedly, the functioning of the named governmental institution had been directly and very adversely affected by both those peculiarities, and only the nuns at the Intercession of Theotokos convent gained an advantage from that extraordinary situation. The publication of primary historical sources describing Ivan Karlov’s banishment complements the study.